Анализа корелације ризика између сировог адионектина (АПН), Д-димера (ДД) и нейтрофил-лимфоцитног односа (НЛР) и прогнозе инфекције језичка ујања дијабетичког стопала: Ефекти серума АПН, Д-Д и НЛР на прогнозу инфекције дијабетичког улкуса стопала - Guo, Guodong; Zhang, Xiaohui; Fang, Peng; Li, Kangkanng; Wang, Chaoyang; Liu, Gang; Ma, Huijuan (Journal of Medical Biochemistry, 2025)
Objective: Investigating the connections between diabetic foot ulcer infection patients' prognosis and disease severity, we measured serum adiponectin (APN), D-dimer (D-D), and the neutrophil-to-lymphocyte ratio (NLR).Methods: A total of 292 patients with diabetic foot ulcer infection admitted to our hospital from February 2024 to February 2025 were selected and divided into mild (n=95), moderate (n=139) and severe (n=58) patients according to the severity of the disease. The levels of serum APN, D-D and the NLR in patients with different severity levels were compared. To analyze serum APN, D-D and the NLR, patients were followed up for one year, and the prognoses of the patients were statistically analyzed.Results: Comparisons of the serum APN, D-D and NLR levels among patients with different severity, and the serum APN levels in moderate conditions were lower than those in patients with mild conditions (P
Keywords: дијабетички чир стопала; Адипонектин (АПН); Д-димер (Д-Д); Саоодношение неутрофила и лимфоцита (NLR)